Assessment of Green Supply Chain Management Practices on Sustainable Business in Ethiopia - Lemma Tadese Boson; Zenebe Elemo; Adisu Engida; Shashi Kant (Research Synergy Press, 2023)
Evaluating organisational performance from the perspective of green paradigms is essential as